A prospective population-based study of maternal, fetal, and neonatal outcomes in the setting of prolonged labor, obstructed labor and failure to progress in low- and middle-income countries. Issue 2 (December 2015) - Harrison, Margo; Ali, Sumera; Pasha, Omrana; Saleem, Sarah; Althabe, Fernando; Berrueta, Mabel; Mazzoni, Agustina; Chomba, Elwyn; Carlo, Waldemar; Garces, Ana; Krebs, Nancy; Hambidge, K; et al.
Abstract Background This population-based study sought to quantify maternal, fetal, and neonatal morbidity and mortality in low- and middle-income countries associated with obstructed labor, prolonged labor and failure to progress (OL/PL/FTP). Methods A prospective, population-based observational study of pregnancy outcomes was performed at seven sites in Argentina, Guatemala, India (2 sites, Belgaum and Nagpur), Kenya, Pakistan and Zambia. Women were enrolled in pregnancy and delivery and 6-week follow-up obtained to evaluate rates of OL/PL/FTP and outcomes resulting from OL/PL/FTP, including: maternal and delivery characteristics, maternal and neonatal morbidity and mortality and stillbirth. Results Between 2010 and 2013, 266, 723 of 267, 270 records (99.8%) included data on OL/PL/FTP with an overall rate of 110.4/1000 deliveries that ranged from 41.6 in Zambia to 200.1 in Pakistan. OL/PL/FTP was more common in women aged <20, nulliparous women, more educated women, women with infants >3500g, and women with a BMI >25 (RR 1.4, 95% CI 1.3 – 1.5), with the suggestion of OL/PL/FTP being less common in preterm deliveries. Protective characteristics included parity of ≥3, having an infant <1500g, and having a BMI <18. Women with OL/PL/FTP were more likely to die within 42 days (RR 1.9, 95% CI 1.4 – 2.4), be infected (RR 1.8, 95% CI 1.5 – 2.2), and have hemorrhage antepartum (RR 2.8, 95% CI 2.1 – 3.7) or postpartum (RR 2.4, 95% CI 1.8 – 3.3). They were also more likely to have a stillbirth (RR 1.6, 95% CI 1.3 – 1.9), a neonatal demise at < 28 days (RR 1.9, 95% CI 1.6 – 2.1), or a neonatal infection (RR 1.2, 95% CI 1.1 – 1.3). As compared to operative vaginal delivery and cesarean section (CS), women experiencing OL/PL/FTP who gave birth vaginally were more likely to become infected, to have an infected neonate, to hemorrhage in the antepartum and postpartum period, and to die, have a stillbirth, or have a neonatal demise. Women with OL/PL/FTP were far more likely to deliver in a facility and be attended by a physician or other skilled provider than women without this diagnosis. Conclusions Women with OL/PL/FTP in the communities studied were more likely to be primiparous, younger than age 20, overweight, and of higher education, with an infant with birthweight of >3500g. Women with this diagnosis were more likely to experience a maternal, fetal, or neonatal death, antepartum and postpartum hemorrhage, and maternal and neonatal infection. They were also more likely to deliver in a facility with a skilled provider. CS may decrease the risk of poor outcomes (as in the case of antepartum hemorrhage), but unassisted vaginal delivery exacerbates all of the maternal, fetal, and neonatal outcomes evaluated in the setting of OL/PL/FTP.